Diagnostic value of bronchoalveolar lavage in the subset of patients with negative sputum/smear and mycobacterial culture and a suspicion of pulmonary tuberculosis. (May 2019) - Ahmad, Mushtaq; Ibrahim, Wanis H.; Sarafandi, Sabir Al; Shahzada, Khezar S.; Ahmed, Shakeel; Haq, Irfan Ul; Raza, Tasleem; Hameed, Mansoor Ali; Thomas, Merlin; Swehli, Hisham Ab Ib; Sattar, Hisham A.
Highlights: The diagnostic value of bronchoalveolar lavage in the subset of patients with both negative sputum/smear and culture is seldom reported. Bronchoalveolar lavage should be pursued as a useful diagnostic tool for suspected pulmonary tuberculosis cases when sputum/smear and culture are negative. Bronchoalveolar lavage mycobacterial culture and polymerase chain reaction provided the highest diagnostic yield. Higher yield is associated with positive QuantiFERON-TB Gold In-Tube test, positive Purified Protein Derivative skin test, upper zone abnormality on chest radiograph or those from the Indian subcontinent. Abstract: Background: The diagnostic value of bronchoalveolar lavage in patients with negative sputum/smear for tuberculous bacilli has been well studied. However, its value in the subset of patients with both negative sputum/smear and culture is seldom reported. Methods: A retrospective study of patients referred for diagnostic bronchoscopy for the suspicion of pulmonary tuberculosis during the period from April 1st, 2015 to March 30th, 2016, and who had negative sputum/smear and culture for tuberculous bacilli. Results: One hundred and ninety patients fulfilled the inclusion criteria. Bronchoalveolar lavage detected further 61/190 (32.1%) pulmonary tuberculosis cases. Bronchoalveolar lavage mycobacterial culture and polymerase chain reaction (positive in 60/190 (31.6%) and 58/190 (30.5%) of patients respectively) provided the highest diagnostic yield, whereas direct smear provided the lowest yield. Bronchoalveolar lavage had a sensitivity of 89.7%, a specificity of 100%, a positive predictive value of 100%, a negative predictive value of 94.6%, and a test accuracy of 96.3% in suspected pulmonary tuberculosis cases with negative sputum/smear and culture. Positive bronchoalveolar lavage yield for tuberculosis was significantly associated with a positive QuantiFERON-TB Gold In-Tube test, positive purified protein derivative skin test, radiological evidence of upper zone abnormality and patient's origin being from the Indian subcontinent. Conclusion: Bronchoalveolar lavage should be pursued as a useful diagnostic tool for suspected pulmonary tuberculosis cases when sputum/smear and culture are negative. Its value is higher in the subset of patients with positive QuantiFERON-TB Gold In-Tube test, positive purified protein derivative skin test, upper zone abnormality on radiograph or being from the Indian subcontinent.